Transcranial magnetic stimulation to probe the role of the supplementary motor area in tics - Conelea, Christine A.; Wellen, Brianna C. M.; Francis, Sunday M.; Mueller, Bryon A.; Jacob, Suma; Lim, Kelvin; Greenberg, Benjamin D. (Frontiers in Human Neuroscience, 2025)
IntroductionSupplementary motor area (SMA) hyperactivity is thought to be a key neural mechanism in tics. This study probed SMA’s role in tic expression, voluntary tic control, and premonitory urge experiences using one session of 1 Hz “inhibitory” repetitive transcranial magnetic stimulation (rTMS) targeting SMA in a repeated measures, small-N experimental design.MethodsYouth with Tourette Syndrome (TS) ages 12—17 years (N = 14) completed a clinical assessment and MRI to localize SMA. The video-based Tic Suppression Task (TST) quantified tic frequency and urges during conditions of Free-to-Tic, Suppression, and Suppression+Reward. The TST was followed by randomly assigned active 1 Hz (n = 8) or sham rTMS (n = 6) and TST repetition post-stimulation.ResultsActive rTMS led to greater tic frequency reductions during Free-to-Tic (d = 0.34) and Suppression+Reward (d = 0.24) but not Suppression (d = 0.0). A stronger effect size for active rTMS was observed in both suppression conditions (d = 0.26, d = 0.63) when excluding participants classified as baseline “strong suppressors” (n = 5). Urges did not differ group-wise for Free-to-Tic (d = 0.09) but decreased more following active rTMS in both suppression conditions (d = 0.19, d = 0.52).DiscussionOverall, results suggest that the acute aftereffects of active 1 Hz rTMS to SMA may include reduced natural tic frequency, improved tic controllability, and lower urge intensity, especially while engaged in suppression efforts. Results are consistent with prior literature pointing to SMA hyperactivation in TS and suggests the potential therapeutic value of rTMS.